PENINGKATAN HASIL BELAJAR KOGNITIF PESERTA DIDIK MENGGUNAKAN QUANTUM LEARNING TEKNIK MEMORI PADA MATA PELAJARAN BAHASA INDONESIA - Trisdianti, Eris; Mangkuwibawa, Hilman; Rifqi Mahmud, Muhammad (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Based on preliminary studies by conducting tests, there are problems in class III MI Al-Musaa'adah Garut regarding the low cognitive outcomes of students in Indonesian language subjects. These problems occur because of the lack of varied learning models so that students are not actively involved in the learning process. Therefore, this study aims to improve the cognitive learning outcomes of students using the Quantum Learning model of memory techniques. This study used Classroom Action Research (PTK) which was conducted in IV cycles. This research was conducted in class III MI Al-Musaa'adah Garut with a total of 25 students. The data collection techniques used were tests and observations. The results of this study indicate that there is an increase in students' cognitive learning outcomes. This can be proven in cycle I the average value of students is 59 with classical completeness of 48%, cycle II the average value of students is 59 with classical completeness of 36%, cycle III the average value of students is 69 with classical completeness of 60%, and in cycle IV the average value of students reaches 74 with classical completeness reaching 80%. This Classroom Action Research was completed because the average results of students reached ≥ 70 in accordance with the KKM and the classical completeness of students reached ≥ 70%. Thus it can be concluded that the application of the Quantum Learning model of memory techniques can improve the cognitive learning outcomes of students in Indonesian language subjects in class III MI Al-Musaa'adah.